2018
DOI: 10.1542/peds.2018-0506
|View full text |Cite
|
Sign up to set email alerts
|

A System-Level Approach to Improve HIV Screening in an Urban Pediatric Primary Care Setting

Abstract: An estimated 25% of all Americans and 41% to 50% of adolescents living with HIV do not know their HIV status. 1 Earlier identification of individuals who are unaware of their HIV status can result in earlier antiretroviral initiation, decreased HIV transmission, and improved HIV outcomes. 2 Universal HIV screening beginning in adolescence is recommended by the Centers for Disease Control and Prevention (CDC) and the United States Preventive Services Task Force. 3, 4 However, pediatric primary care settings hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Similarly, programs in urban primary care networks used dedicated health educators to alleviate physicians' time constraints. 8,26 Concerns about confidentiality are known to be a key barrier to adolescents seeking sexual and reproductive care applicable to HIV screening. A review 10 that synthesized studies about confidentialityrelated factors identified themes relevant to adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, programs in urban primary care networks used dedicated health educators to alleviate physicians' time constraints. 8,26 Concerns about confidentiality are known to be a key barrier to adolescents seeking sexual and reproductive care applicable to HIV screening. A review 10 that synthesized studies about confidentialityrelated factors identified themes relevant to adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review 18 summarizing HIV screening programs in US PEDs 19–25 showed that all were conducted at large academic centers or children's hospitals, and several had dedicated staff resources and funding. Similarly, programs in urban primary care networks used dedicated health educators to alleviate physicians' time constraints 8,26 …”
Section: Discussionmentioning
confidence: 99%
“…Quality improvement projects performed in various primary care and specialist settings have increased HIV screening rates but the effects have been either small and not population based. [17][18][19] Using concepts of audit and feedback to improve practice outcomes, we identified a need for quality improvement and an attainable goal to increase HIV screening rates within our KP healthcare system. 20 21 Using successive rounds of real-time audit and feedback in the form of a HIV screening report card, cohort PCPs were given a summary of their clinical performance and were compared with their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Plan-do-study-act (PDSA) cycles are an innovative method for evaluating and refining interventions to improve workflow and clinical outcomes. 7 PDSA provides a structured framework for testing changes on a small scale and rapidly applying what is learnt to inform interventions before large-scale implementation. 8 Recent findings demonstrate how adaptations to quality improvement efforts are necessary when facing crisis situations like the COVID-19 pandemic to allow a quick response while optimising patient safety.…”
Section: Objectivesmentioning
confidence: 99%
“…Plan–do–study–act (PDSA) cycles are an innovative method for evaluating and refining interventions to improve workflow and clinical outcomes 7. PDSA provides a structured framework for testing changes on a small scale and rapidly applying what is learnt to inform interventions before large-scale implementation 8.…”
Section: Objectivesmentioning
confidence: 99%